KONJUNGSI DALAM BAHASA NIAS RAGAM SELATAN DIALEK HILIZIHO ́NO ́ DI KECAMATAN FANAYAMA - Trisnawati Nehe (Universitas Nias Raya, 2021)
This research is motivated by the fact that each language has its own uniqueness, namely the Nias language has a word class like the word class in Indonesian, one of which is a conjunction class. It turns out that the Nias language uses conjuntions like those used in Indonesian. In addition, the researcher wants to introduce Nias Conjunctions to Nias language user. The purpose of this study is to describe (coordinative and subordinating conjunctions) the Southern Nias language in Hilizihono, Fanayama District. Thi study uses a qualitative approach with a descriptive method. Based on the results of the research, the researcher found several coordinating conjunctions and subordinating conjunctions in the Southern Nias language in Hilizihono, Fanayama District. The coordinating conjunctions found were 9 quotes and the subordinating conjunctions were 11 quotes. So, the Southern Nias language in Hilizihono, Yanayama District, consist of 20 quotations. In conclusion, the types of conjunctions with 11 quotations. The data of the findings of this study can be used as a guide for the community and as learning in school students. This can be applied to lacal content learning materials (mulok), especially the Nias language. Suggestions for teachers and prospective theachers should use this research as a lesson to increase students’ knowledge about coordinating conjunctions and subordinating conjunctions in the Nias language. For the community, this research can serve as a guideline for studying the Nias language. For further researchers, it is better to use this research as a reference material for relevant research.